Factors associated with withdrawal of the anti‐TNFα biologics in the treatment of rheumatic diseases: data from the Hong Kong Biologics Registry. (30th December 2013) - Mok, Chi Chiu; Chan, Ka Yan; Lee, Ka Lai; Tam, Lai Shan; Lee, Ka Wing; ,
Abstract: Objectives: To study the factors associated with withdrawal of the and tumor necrosis factor alpha (anti‐TNFα) biologics in the treatment of rheumatic diseases. Method: Data from the Hong Kong Biologics Registry were retrieved. The cumulative rates of withdrawal of different biological agents were studied by Kaplan–Meier plot and the incidence of serious adverse events (SAEs) was calculated. Factors associated with the withdrawal of the anti‐TNFα agents were studied by Cox regression. Results: Between 2005 and 2013, 2059 courses of biologics were used in 1345 patients. After 3454 patient‐years, 1171 (57%) courses were terminated because of clinical inefficacy (38.1%), SAEs (22.3%) and financial reasons (15.9%). The most frequent SAEs (per 100‐patient‐years) were allergy (2.90), serious infections (1.34), tuberculosis (0.93) and infusion/injection site reaction (0.75). Among the anti‐TNFα agents, the cumulative probability of drug withdrawal for either inefficacy or SAEs in 5 years was highest with infliximab (IFX) (64.5%), followed by etanercept (ETN) (44.2%) and adalimumab (ADA) (36.9%). The incidence of serious infections and tuberculosis (per 100 patient‐years) for IFX, ETN and ADA users was 1.99, 0.85 and 0.63; and 1.68, 0.43 and 0.85, respectively. Infusion/injection site reaction was highest with IFX (1.38/100 patient‐years). Cox regression revealed increasing age, female sex, not having a diagnosis of spondyloarthritis (SpA) and IFX use were significantly associated with drug withdrawal for either inefficacy or SAEs. Rheumatoid arthritis (RA) had the highest hazard ratio for drug withdrawal but SpA was favorable for drug retention, after adjustment for age, sex, disease duration and the choice of anti‐TNFα agents. Conclusions: In our registry, the retention rate of the anti‐TNFα agents was lowest but the incidence of tuberculosis, serious infections and infusion reaction was highest with IFX. Older female patients with RA and the use of IFX were independently associated with drug withdrawal.